1982
DOI: 10.1007/bf02372457
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the efficacy of a phytohormone producing phosphate solubilizingBacillus firmus in augmenting paddy yield in acid soils of Nagaland

Abstract: Summary A super strain of Bacillusfirmus (NCIM-2636) producing a phytohormone, indole-3-acetic acid, in addition to its high ability to solubilize insoluble inorganic phosphates were applied in acid soils of Nagaland, India. Rice (Oryza sativa L.) variety Jaya and IR-8 were grown in kharif season in two successive years 1980 and 1981. After proper manuring the soils received single super phosphate (S.S.P.) and Mussoorie Rock phosphate (R.P.) separately at different doses. Yield of crop in both the years incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Phosphorus solubilizing bacteria and silicate bacteria play a important role in plant nutrition through the increase in P and K uptake by plant (Datta et al, 1982;Nyanikova et al, 2002;Neelamet et al (2016). Han and Lee (2006) found that the coinoculation of PSB and KSB in combination with direct application of rock P and K materials into the soil increased in N, P and K uptake, photosynthesis and the yield of eggplant grown on P and K limited soil.…”
Section: Phosphorus Content Of Seedsmentioning
confidence: 99%
“…Phosphorus solubilizing bacteria and silicate bacteria play a important role in plant nutrition through the increase in P and K uptake by plant (Datta et al, 1982;Nyanikova et al, 2002;Neelamet et al (2016). Han and Lee (2006) found that the coinoculation of PSB and KSB in combination with direct application of rock P and K materials into the soil increased in N, P and K uptake, photosynthesis and the yield of eggplant grown on P and K limited soil.…”
Section: Phosphorus Content Of Seedsmentioning
confidence: 99%
“…P solubilizing bacteria and silicate bacteria play an important role in plant nutrition through the increase in P and K uptake by the plant [3]. Application of Phosphate solubilizing microorganisms have been used as P-biofertilizer for crop cultivation [11] [12]. Silcate bacteria provided less polluting and less energy-consuming approaches [13] widely used in improvement of available K for assimilation by plants, and removal of impurities from minerals [14].…”
Section: Bacteria Isolation and Colony Characteristicmentioning
confidence: 99%
“…It can be improved by many ways, of which the pre-sowing seed management technique plays a vital role. Among the pre-sowing seed management techniques, the seed treatment with the biofertilizers is one of the important method by which the yield can be improved by 5 to 30 per cent (Datta et al, 1982). Use of these effective microorganisms as a presowing seed treating agent is considered to be ecologically sound and beneficial to both seed and environment.…”
Section: Introductionmentioning
confidence: 99%